1994
DOI: 10.1002/jlb.55.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interferon-α-inducible cellular genes in human immunodeficiency virus-infected monocytes

Abstract: Cellular mechanisms that control susceptibility to opportunistic infection in human immunodeficiency virus (HIV)-infected individuals remain poorly understood. HIV may induce certain cellular genes that restrict HIV replication and protect cells against other superinfecting viral pathogens. Indeed, HIV-infected monocytes resist infection by vesicular stomatitis virus (VSV). HIV-induced VSV interference in monocytes increases with time after HIV infection. Such interference was evident 6 h after HIV infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 49 publications
4
24
0
2
Order By: Relevance
“…Although previous experiments have failed to find active IFN in scrapie (34), up-regulation of IFN-related genes in CJD might involve other factors. This latter type of IFNindependent transcriptional induction has already been noted in monocytes infected with HIV (35); it can also be caused by direct interactions between viral proteins and host transcriptional machinery (36). Conventional viral elements could conceivably be involved in the transcriptional program observed in CJD microglia, given the continued failure of PrP-res to elicit all of the changes associated with infection.…”
Section: Discussionmentioning
confidence: 78%
“…Although previous experiments have failed to find active IFN in scrapie (34), up-regulation of IFN-related genes in CJD might involve other factors. This latter type of IFNindependent transcriptional induction has already been noted in monocytes infected with HIV (35); it can also be caused by direct interactions between viral proteins and host transcriptional machinery (36). Conventional viral elements could conceivably be involved in the transcriptional program observed in CJD microglia, given the continued failure of PrP-res to elicit all of the changes associated with infection.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, it had been demonstrated earlier, in a cellular model, that IFN-a inhibited HBV replication by reducing transcription of viral genes driven by the HBV enhancers (Tur-Kaspa et al, 1990). In a previous model, Baca et al (1994) showed that HIV-1 was able to induce expression of antiviral IFN-astimulated genes 29-59 oligo-adenylate synthetase and MxA as a means of protecting cells against other superinfecting viral pathogens (Baca et al, 1994). Such a mechanism may be suggested in an HBV/HDV context, and the effects could be exerted in an autocrine or paracrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 tat can inhibit PKR, an antiviral effector molecule that, like Mx, is induced by IFN-␣/␤ (94). Monocytes from HIV-infected patients can produce Mx after in vitro HIV infection and thereby effectively prevent superinfection of these cells by other viruses without interfering with the replication of HIV (6). It has recently been demonstrated that Mx had no inhibitory effect on the replication of another complex human retrovirus (90).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of IFN-␣/␤ is transient, while Mx continues to be expressed after IFN-␣/␤ are no longer detectable (53,54). In addition, Mx can be induced independently of IFN-␣/␤ in monocytes isolated from HIV-1-infected patients (6). In fact, viral proteins alone, in the absence of viral replication, can induce Mx (43,52).…”
Section: Discussionmentioning
confidence: 99%